Circularly polarized luminescence of coordination aggregates. Issue 5 (11th February 2022) - Gong, Zhong‐Liang; Li, Zhong‐Qiu; Zhong, Yu‐Wu
Abstract: The development and applications of materials with efficient circularly polarized luminescence (CPL) have become an interdisciplinary frontier research topic. We summarize herein the recent advance in the development and applications of CPL‐active aggregates based on metal‐ligand coordination materials (termed as "coordination aggregates"). The materials surveyed are classified as aggregates of small‐molecular metal complexes, which include monocomponent assemblies of Pt(II) complexes and other complexes and binary aggregates of metal complexes, and CPL‐active metal‐ligand coordination helicates, polymers, and frameworks. The efforts in improving the dissymmetry luminescence factors and quantum yields of these materials and the use of the aggregation strategy in enhancing the performance of isolated molecules are discussed. The recent applications of chiral metal complexes in circularly polarized organic light‐emitting diodes (OLEDs) based on solution‐ or evaporation‐processed procedures are surveyed. In addition, the uses of lanthanide complexes in CPL‐contrast imaging and as CPL probes are highlighted. The common discussion on the mechanism of aggregation‐enhanced CPLs and a perspective on future works of CPL‐active coordination aggregates are finally given. Abstract : The recent progress in the development of circularly polarized luminescence (CPL)‐active aggregates of metal‐ligand coordination materials is summarized, including those based on discrete chiral metal complexes, chiral metal‐ligand helicates, and coordination polymers and frameworks. The applications of these materials in circularly polarized organic light‐emitting diodes and CPL‐contrast imaging and probes are further discussed.